Factores sociodemograficos y nivel de conocimiento sobre estimulación prenatal en primigestas del distrito de Moche 2009 - Alva Valera, María Ysabel (2009)
This research study is a descriptive cross-sectional correlational and it was conducted in the district of Moche in the province of Trujillo, La Libertad department, during the months of August to October of 2009 with the aim of determining the relationship of sociodemographic factors age, educational level, occupation and source with the level of knowledge about prenatal stimulation of primigravid. The sample consisted of 85 primigravid selected according to established inclusion criteria. Data collection was obtained by applying the tool called: Scale to assess socio-demographic factors and level of knowledge about prenatal stimulation primigravid (EVFSNCPEP) was used for personal interviews, respecting the ethical principles of anonymity, confidentiality and free participation. The collected data were tabulated, processed in SPSS version presented in tables 15 and single and double entry with numerical frequencies and percentages, as well as graphics. The analysis of the relationship of the factors was conducted by independent testing criteria Chi square (X2). Finding the followig conclusions: 1. Of the rotal of first time study, 50.6 percent for the group of primigravid adolescents, 54.1 percent have secondary education level, the 92.9 percent work in their home and 71.8 percent are from the coast. 2. The 62.4 percent of primigravid have a partially adequate level of knowledge about prenatal stimulation, 37.6 percent had a level of appropriate knowledge, We find no primigravid with inadequate level of knowledge. 3. The Sociodemographic factors of primigravid that are significantly related to the level of knowledge about prenatal stimulation are: educational attainment and origin. 4. Sociodemographic factors of primigravid not significantly related to level of knowledge about prenatal stimulation are age and occupation.